Controls of greenhouse gases production and soil nutrients dynamics in the Lena River Delta, Northeastern Siberia - Galera, Leonardo de Aro (Journal of Geophysical Research: Biogeosciences, 2024)
The permafrost stores vast amounts of organic carbon. As permafrost thaws due to global warming, previously frozen organic matter become accessible to microbial decomposition. This process releases greenhouse gases like carbon dioxide (CO2) and methane (CH4) creating a positive feedback loop, where increased greenhouse gas emissions lead to further warming and subsequent thawing, a process known as the permafrost carbon-climate feedback. In this thesis two key research gaps in the understanding of the permafrost carbon-climate feedback are addressed with studies from sites in the Lena River Delta, Northeastern Siberia, Russia. The second chapter assessed the determining factors for the ratio between in situ CO2 to CH4 production in the polygonal tundra. This is an important topic about the permafrost carbon-climate feedback, since CH4 has a 28-fold higher global warming potential than CO2 and it is crucial to determine the factors modulating the partitioning between CO2 and CH4 fluxes from organic matter decomposition in the Arctic. In this study I quantified the CO2:CH4 production ratios of soil organic matter decomposition in wet and dry tundra soils in Samoylov Island, Lena River Delta, by using CO2 fluxes from clipped plots and in situ CH4 fluxes from vegetated plots. The results show that active layer depth and soil temperature were the main factors controlling these ratios, which decreased towards the end of the end of the growing season, when the active layer was deep and warm enough for methanogenesis. CH4 production was associated with subsoil (40 cm) temperature, while heterotrophic respiration was related to topsoil (5 cm) temperatures, mainly due to the mostly oxic environment of topsoil, inducing aerobic CO2 production, and the anoxic environment of the subsoil, inducing CH4 production. The third chapter assessed the effect of thawing and warming on the availabilities of phosphorus (P) and potassium (K) in incubated soils of Kurungnakh Island, Lena River Delta. The fate of soil nutrients in ...